Postoperative complications of umbilical loop colostomy for anorectal malformations in neonates compared with the conventional abdominal stoma: a non-randomized study - Tatsuma Sakaguchi; Yoshinori Hamada; Takeshi Shirai; Hiroshi Hamada; Yusuke Shigeta; Yusuke Nakamura; Takashi Doi (BMJ Publishing Group, 2019)
Background We previously reported a pilot study of temporary umbilical loop colostomy for neonates with intermediate-type anorectal malformations (ARM) and recommended this technique because of its cosmetic excellence. We herein report the postoperative complications of umbilical stomas (US) compared with traditional abdominal stomas (AS).Methods From our institutional prospective database, we analyzed the patients with ARMs who underwent stoma creation at Kansai Medical University Hospital from January 1995 to November 2016. The surgical technique used to create the US had been performed since 2004.Results US and AS were made for 12 and 27 patients with ARMs, respectively. The postoperative complication rates in patients who underwent US and AS had no significant difference (17% and 11%, p=0.6). The complications comprised a wound infection (one case of US), ileus (one case each of US and AS), mucosal prolapse (one case of AS), and depression (one case of AS). No emergency surgery was required for these complications.Conclusion For patients with ARMs, the umbilicus appears to be a safe alternative site for temporary loop colostomy.